Pathogenicity of a novel bovine adenovirus type 3 with a natural deletion partial fiber gene in BALB/c mice - Li, Qian; He, Shufan; Zou, Yuantong; Yue, Hua; Tang, Cheng; Liu, Jie (Frontiers in Veterinary Science, 2023)
Objective A novel Bovine adenovirus type 3 (BAdV-3) with a natural deletion partial fiber gene was isolated in 2020 and named BO/YB24/17/CH. The objective of this study was to understand the pathogenicity of this virus. Methods Thiry-two 3-week-old BALB/c mice were divided into three experimental groups and a control group. Mice in the experimental groups were intranasally inoculated with virus, and mice in the control group were inoculated with MDBK cell supernatant. Mice were weighed and clinically examined daily for appearance of any clinical signs. Three infected mice and one control mouse were euthanized at 1, 3, 5, 7, 9, 11, 13, and 15 days after inoculation. Tissue samples were collected for histopathological examination, immunohistochemical staining, and detection of the replication dynamics of virus. Results All infected mice developed mild clinical signs such as lethargy, weight loss, loss of appetite, and a rough hair coat, and gross lesions were observed as pulmonary punctate hemorrhage, lobular atrophy and splenomegaly. Histopathological examination revealed thickening of alveolar septa and mildly dilated splenic nodules and blurred red-white medullary demarcation in the spleen. Immunohistochemical results further confirmed that the production of the above lesions was due to viral infection. Importantly, unlike previously reported BAdV-3 detection only in the lungs and trachea, this isolate could be detected in multiple organs such as the heart, liver, spleen, kidney, and even blood by virus isolation and titration and real-time PCR methods. Clinical significance This study provides further insight into the pathogenicity of the fiber region deletion strain BO/YB24/17/CH in BALB/c mice, which provides a reference for the prevention and control of BAdV-3 as well as the development of vaccines.